Preclinical Pharmacokinetics and Dosimetry of an 89Zr Labelled Anti-PDL1 in an Orthotopic Lung Cancer Murine Model - Krache, Anis; Fontan, Charlotte; Pestourie, Carine; Bardiès, Manuel; Bouvet, Yann; Payoux, Pierre; Chatelut, Etienne; White-Koning, Melanie; Salabert, Anne-Sophie (Frontiers in Medicine, 2022)
Anti-PDL1 is a monoclonal antibody targeting the programmed death-cell ligand (PD-L1) by blocking the programmed death-cell (PD-1)/PD-L1 axis. It restores the immune system response in several tumours, such as non-small cell lung cancer (NSCLC). Anti-PDL1 or anti-PD1 treatments rely on PD-L1 tumoural expression assessed by immunohistochemistry on biopsy tissue. However, depending on the biopsy extraction site, PD-L1 expression can vary greatly. Non-invasive imaging enables whole-body mapping of PD-L1 sites and could improve the assessment of tumoural PD-L1 expression. Methods Pharmacokinetics (PK), biodistribution and dosimetry of a murine anti-PDL1 radiolabelled with zirconium-89, were evaluated in both healthy mice and immunocompetent mice with lung cancer. Preclinical PET (μPET) imaging was used to analyse [89Zr]DFO-Anti-PDL1 distribution in both groups of mice. Non-compartmental (NCA) and compartmental (CA) PK analyses were performed in order to describe PK parameters and assess area under the concentration-time curve (AUC) for dosimetry evaluation in humans. Results Organ distribution was correctly estimated using PK modelling in both healthy mice and mice with lung cancer. Tumoural uptake occurred within 24 h post-injection of [89Zr]DFO-Anti-PDL1, and the best imaging time was at 48 h according to the signal-to-noise ratio (SNR) and image quality. An in vivo blocking study confirmed that [89Zr]DFO-anti-PDL1 specifically targeted PD-L1 in CMT167 lung tumours in mice. AUC in organs was estimated using a 1-compartment PK model and extrapolated to human (using allometric scaling) in order to estimate the radiation exposure in human. Human-estimated effective dose was 131 μSv/MBq. Conclusion The predicted dosimetry was similar or lower than other antibodies radiolabelled with zirconium-89 for immunoPET imaging.